2020
DOI: 10.1371/journal.pone.0237940
|View full text |Cite
|
Sign up to set email alerts
|

Double antibody pairs sandwich-ELISA (DAPS-ELISA) detects Acidovorax citrulli serotypes with broad coverage

Abstract: Acidovorax citrulli, a seedborne bacterium and quarantine pest, causes the devastating bacterial fruit blotch disease in cucurbit plants. Immunological assays such as ELISA are widely used in routine field inspections for this bacterium. However, to the best of our knowledge, none of the currently available monoclonal antibodies (MAbs) can detect all common A. citrulli strains. We therefore aimed to produce a panel of MAbs and to develop an ELISAbased method capable of detecting all A. citrulli strains. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…The DAS-ELISA assay established by using two mAbs ensured the test sensitivity and specificity when detecting the CaEno in the supernatant samples (Himananto et al 2020). Our findings suggested that the main source of extracellular CaEno might not be simply derived from only fungal lysis.…”
Section: Discussionmentioning
confidence: 75%
“…The DAS-ELISA assay established by using two mAbs ensured the test sensitivity and specificity when detecting the CaEno in the supernatant samples (Himananto et al 2020). Our findings suggested that the main source of extracellular CaEno might not be simply derived from only fungal lysis.…”
Section: Discussionmentioning
confidence: 75%